The new girl - Andelfinger, Nicole; Pascal, Francine; Montgomery, Warren; (Illustrator); Bell, Andrea; Jackson, Remus; Lynde, Lyle; Pascal, Francine; Whittle, Knack (RH Graphic, 2025)
"When a new girl moves to Sweet Valley, the Wakefields are ready to welcome her to town--unfortunately for Jessica and Elizabeth, Brooke Dennis seems to want nothing to do with them. She's the meanest girl they've ever met! The last thing Jessica wants to do is show her around or help her at school. Elizabeth wonders if maybe there is more going on with Brooke--there has to be a reason she's so mad all the time, right?"--
Keywords: Fiction; Transfer students; Fiction; Moving (Households); Fiction; Family problems; Fiction; Sisters; Fiction; Middle schools; Fiction; Schools; Fiction; Cartoons and comics; Graphic novels; Friendship; Fiction; Comic books, strips, etc; Comic books, strips, etc; Twins; Comic books, strips, etc; Sisters; Transfer students; Comic books, strips, etc; Moving, Household; Twins; Comic books, strips, etc; Comic books, strips, etc; Friendship in children; Comic books, strips, etc; Middle schools; Comic books, strips, etc; Schools; Dysfunctional families; School comics; Graphic novel adaptations; Graphic novels